Spectroscopic and theoretical investigation of the conformational space of a pyrazolo-thiazole precursor of extended dipole diazafulvenium methide intermediates - Nunes, Cláudio M. (2009)
http://www.sciencedirect.com/science/article/B6TGS-4V88FW3-1/2/a0eb253493e1ccafe49b75247f2ded74